The Death Penalty in Indonesian Corruption: An Analysis of Normative Constructions and Gaps in Law Enforcement Practices through a Literature Review - Mohamad Yunus Laia; Redyanto Sidi (CV. Era Digital Nusantara, 2026)
This study analyzes the normative construction of the death penalty for corruption in Indonesia and identifies the gap between legal norms and law enforcement practice. The research focuses on how criminal law literature constructs the legitimacy of capital punishment, why the sanction has never been applied in practice, and how the death penalty is positioned within the criminal law system. Using a non-Systematic Literature Review method, this study adopts qualitative doctrinal and socio-legal approaches to relevant indexed journal articles. The collected data are examined through thematic synthesis to map patterns of normative argumentation, judicial reasoning, and orientations of criminal law policy reflected in the literature. The findings demonstrate that scholarly works consistently acknowledge the normative legitimacy of the death penalty for corruption based on juridical, philosophical, and theoretical considerations. Nevertheless, the literature simultaneously reveals the complete absence of its application in judicial decisions. This gap is explained by judicial discretion, weaknesses in norm formulation, and the pragmatic orientation of criminal law policies that prioritize flexibility over severity. The study further finds that the death penalty operates primarily as a symbolic norm rather than as an effective operational sanction. Consequently, the persistent divergence between normative recognition and practical non-application reflects a broader normative dysfunction within Indonesia’s corruption criminal law regime. This research contributes conceptually to debates on criminal law effectiveness globally.